Praktik Manajemen Laba Setelah Penerapan PSAK 72 Pada Sektor Properti Dan Real Estat Di Indonesia - Dedek Catur Amung Saputra; Liza Alvia (Institut Nalanda, 2024)
This study aims to analyze whether there are differences in earnings management practices after the adoption of IFRS 15 as contained in PSAK 72. The population of this study uses the property and real estate sector listed on the Indonesia Stock Exchange with the analysis period 2018-2021. Hypothesis testing was carried out using a non-parametric mean difference test, namely the Wilcoxon signed rank test. The results of this study indicate that there is a significant difference in the decline in earnings management practices after the implementation of PSAK 72. This theme supports that this standard is able to improve revenue recognition and provide more comprehensive guidance regarding contracts with customers so that profits reduce agency risk.